Underserved populations at historically black colleges and universities : the pathway to diversity, equity, and inclusion - Davis, Cheron H.; Hilton, Adriel A.; Outten, Donavan L. (Bingley, U.K. : Emerald Publishing Limited, 2018)
This book focuses on the lived experiences of underserved student and faculty populations at historically Black colleges and universities (HBCUs) and the implications these experiences have for higher education policy. Contributors discuss the contexts and experiences of students and faculty who navigate the political and social spaces of HBCUs while supporting healthy personal and robust professional goals. The stigmas and social nuances that plague students and faculty of color do not dissolve with their arrival at an HBCU, but rather they transform into a new set of challenges that demand the attention of researchers. Taking into account institutional supports, identity development, and socialization patterns, this book sheds light on what the experiences of higher education's "outsiders" mean for future research and practice, while emphasizing issues of diversity, equity, and inclusion.
Prelims -- Bringing the "othered" back in: building the case for diversity, equity, and inclusion at HBCUs -- A balancing act: being first still, and faculty at an HBCU -- Serving students, faculty, and notice: student cooperation, faculty collaboration, and institutional counter-narration at a southern flagship HBCU -- The contemporary role of the HBCU in diversity, equity, and inclusion in the absence of ongoing historical relevance -- Just let us be great! mentoring students at an HBCU -- White faces in black spaces: examining facultystudent engagement for white doctoral student success at historically black colleges and universities -- Religious minority students at HBCUs -- Thursdays at five thirty-five -- The role of HBCUs in tackling issues of diversity, equity, and inclusion -- Challenging cultural norms at HBCUs: how perceptions impact lgbtq students' experiences -- Afrocentric worldview, hetero-normative ethos and black LGBTQ intellectuals matriculating through afrocentric psychology programs at historically black colleges/universities (HBCUs) -- Providing support for non-black students and faculty at HBCUs: a promising approach for senior academic and student affairs officers (SASAOs) -- Envisioning equity: women at the helm of HBCU leadership -- Bad board behaviors: undermining growth and development at historically black colleges and universities -- What's next? -- Epilogue -- Index.
Includes index.
Print version record
Keywords: African Americans -- Education (Higher); African American universities and colleges -- United States; Educational equalization -- United States; Education -- Multicultural Education; Multicultural education